Shk (a histidine kinase) positively regulates the virulence of Ralstonia solanacearum strain GMI1000 - Xue, Dexing; Kong, Danyu (Frontiers in Microbiomes, 2025)
Quorum sensing (QS) serves as a regulatory system of virulence factors in the Ralstonia solanacearum species complex (RSSC). The two-component system PhcS–PhcQ recognizes QS signals, subsequently activating the transcriptional regulator PhcA and promoting the expression of QS-dependent virulence factors. In this study, we identified a sensor histidine kinase (Shk) in the R. solanacearum strain GMI1000 and uncovered its essential roles in PhcA-dependent virulence. To investigate the functions of Shk in QS-dependent virulence, we generated an shk-deletion mutant (Δshk) and demonstrated that the deletion of shk leads to a lowered production of cellulase, biofilm, and exopolysaccharide. Moreover, the complementation of native shk in Δshk cell restored the QS-dependent phenotypes. However, the swarming motility of Δshk cells was significantly increased compared to the wild-type GMI1000 strain. The Δshk mutant exhibited impaired colonization of R. solanacearum in the xylem vessels of tomato plants, resulting in attenuated pathogenicity of Δshk to tomato plants. Consistent with the results of the virulence assay, the deletion of the shk gene of R. solanacearum led to the downregulation of the phcA, epsB, and cbhA genes in planta, while the expression of fliC was upregulated in the Δshk mutant relative to the wild-type GMI1000 strain. Pull-down assays suggested that RSc0040 functions as a response regulator for the sensor Shk in vivo and in vitro. Collectively, Shk is implicated in the regulation of these QS-dependent virulent factors, thereby contributing to the virulence of R. solanacearum to tomato plants.